2021
DOI: 10.3390/ijerph18136716
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Community in the Face of COVID-19. Discursive Analysis on Vulnerability and Education

Abstract: This article presents the results of research the objective of which was to know the opinion of directors of different educational centers about the management carried out in their centers and the possible difficulties encountered during the suspension of face-to-face classes caused by the first wave of the COVID-19 pandemic. The research method is qualitative, exploratory, descriptive, and inductive. The study sample is made up of 43 managers of educational centers, who were selected by applying an intentiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…This was compounded by a lack of digital skills amongst parents which potentially generated inequalities amongst the pupils. Their findings confirmed that families with more resources were better able to support their children in educational tasks (López-Noguero et al, 2021).…”
Section: Wellbeing and Behaviormentioning
confidence: 60%
“…This was compounded by a lack of digital skills amongst parents which potentially generated inequalities amongst the pupils. Their findings confirmed that families with more resources were better able to support their children in educational tasks (López-Noguero et al, 2021).…”
Section: Wellbeing and Behaviormentioning
confidence: 60%
“…The need to develop online training programs for HCPs has been recognized not only in Japan but also worldwide amid the COVID-19 pandemic, and various challenges have surfaced owing to the rapid digitalization of education [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto al tipo de instituciones que están centrando sus esfuerzos en el estudio de la superación de las desigualdades mediante tecnología, es remarcable el peso de centros de educación superior como la Universidad de Sevilla con 6 artículos (Cabero et al, 2021;Cabero et al, 2020;Cabero et al, 2019;López-Noguero et al, 2021a;López-Noguero et al, 2021b;Padilla-Carmona et al, 2016), la Universidad de Salamanca (Casillas-Martín et al, 2020;Verdugo, 2019;Romo, 2018;Casado-Muñoz et al, 2015), y la Universidad Complutense de Madrid (Tirado et al, 2021;Hernández et al, 2021;Calderón et al, 2020y Vázquez et al, 2015, con cuatro documentos cada una de ellas.…”
Section: Resultsunclassified